Nanocomposites of irradiated polypropylene with clay are degradable?. (January 2016) - Komatsu, L.G.H.; Oliani, W.L.; Lugao, A.B.; Parra, D.F.
Abstract: In nowadays, polypropylene (PP) based nanocomposites containing organically modified montmorillonite (MMT), have gained great attention in the automobilistic industries, construction, paints, packageing, plastic components of the telecommunication industries. The HMSPP (high melt strength polypropylene) is a polypropylene modified by irradiation process, under acetylene atmosphere, in which irradiation occurs in 60 Co gamma source. However, when those materials are submitted to environmental ageing nanocomposites demonstrated high decomposition level after 1 year. This fact can be due to presence the metallic ions present in the montmorillonite. The HMS-PP and the Cloisite 20A (MMT) were mixed in twin-screw extruder using maleic anhydride as compatibilizer. In this work two formulations of nanocomposites at 0.1 and 5 wt% of clay were submitted to the environmental and thermal ageing to analyze the effects of degradation on the HMSPP nanocomposites. The evaluation of thermal properties was analyzed by Differential Scanning Calorimetry (DSC) and the chemical alterations were investigated by Carbonyl Index (CI), through Fourier Transformed Infrared (FTIR) technique. The basal distance was measured by X-ray diffraction (DRX) and the clay elements were analyzed by X-ray Fluorescence (WDXRF). The aim of this work was to understand the effects of degradation of the HMS-PP/clay nanocomposites. Highlights: Nanocomposites of PP were aged under environmental and thermal conditions. Barrier effect of clay platelets was verified on the nanocomposites. Nanocomposites showed more cracks and surface porosity after environmental ageing. Carbonyl indexes were lower in nanocomposites than in the irradiated PP.